IMPLEMENTASI TERAPI MUSIK KLASIK UNTUK MENURUNKAN KECEMASAN PADA IBU HAMIL TRIMESTER III DI KLINIK BIDAN AIDA NOSPITA S.KEB DELI SERDANG - Annisa Rahma Amelia; Purwaningsih Purwaningsih; Nisrina Nisrina (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The third trimester of pregnancy is a period that often causes anxiety among pregnant women due to the approaching labor process. Untreated anxiety may adversely affect the mother's physical and psychological condition and may also pose risks to fetal health. One of the non-pharmacological interventions that can be used to help reduce anxiety is classical music therapy, which provides relaxation and a calming effect. This study aimed to provide nursing care by implementing classical music therapy to reduce anxiety levels among women in the third trimester of pregnancy. This study employed a descriptive method using a case study design with a nursing process approach, including assessment, nursing diagnosis, intervention planning, implementation of classical music therapy, and evaluation. The intervention was conducted on two pregnant women experiencing anxiety. The findings showed that after receiving classical music therapy for three consecutive days, both participants experienced a reduction in anxiety levels. In Case 1, the anxiety score decreased from 5 before the intervention to 2 after the intervention. In Case 2, the anxiety score decreased from 5 before the intervention to 1 after the intervention. The study concludes that classical music therapy is an effective non-pharmacological intervention for reducing anxiety among women in the third trimester of pregnancy. It is recommended that this therapy be incorporated as a complementary intervention in nursing care for pregnant women approaching childbirth.